Force and electromyographic responses of the biceps brachii after eccentric exercise in athletes and non-athletes - Kawczynski, A. (Journal of Human Kinetics, 2019)
The aim of this study was to compare skeletal muscle response to elbow flexors eccentric exercise in athletes and non-athletes. A set of eccentric (ECC) exercises was performed in a group of 12 athletes and 12 non-athlete controls. Maximal isometric force, electromyographic (EMG) activity of the biceps brachii and the resting elbow angle were assessed before, immediately, 48 hours, 5 and 10 days after high-intensity ECC exercises. During the set of the ECC exercises each participant performed 25 eccentric contractions of elbow flexors. Each contraction consisted of lowering a dumbbell from the flexed (elbow joint angle: 50°-)to the extended elbow (elbow joint angle: 180°-)position. The weight of the dumbbell was set at 80% of one-repetition maximum (1RM). The ECC contractions caused a decrease in maximal isometric force in both groups. The variable dropped by 8% in non-athletes and by 24% in athletes. Furthermore, the EMG RMS increased significantly only for non-athletes 10 days after the ECC exercise compared to baseline values. The present study showed different effects of ECC exercise on force and EMG in athletes and non-athletes, indicating a more pronounced force response in athletes and electromyographic response in non-athletes.